Demand uncertainty, product differentiation, and entry timing under spatial competition - Takeshi Ebina; Noriaki Matsushima; Katsumasa Nishide (Osaka University, Institute of Social and Economic Research (ISER), 2017)
We investigate the entry timing and location decisions under market-size uncertainty with Brownian motions in a continuous-time spatial competition duopoly model a la d'Aspremont et al. (1979). Under a sequential equilibrium, the threshold of the follower non-monotonically increases in volatility, which is in stark contrast to the extant results in the real options literature. Also, although the follower's entry timing tends to be late as the volatility becomes amplified, the leader is more likely to increase the degree of product differentiation as the volatility gets higher. Finally, we compare the equilibrium entry decisions with the second-best ones.
Keywords: C73; D81; L11; L13; 330; Location; Hotelling model; Continuous-time model; Entry timing; Real options